Compliance with antimicrobial therapy: Evaluating the related factors - Mandana Moradi; Soudabeh Hamedi-Shahraki; Mahdiyeh Rezayee; Mohsen Verdi (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Uncontrolled and irrational use of antibiotics increases the rate of antimicrobial resistance and treatment failure. Compliance with antibiotics is an important indicator to show how patients use their prescribed drugs and it can explain the relationship between drug administration and treatment outcome that needs to be monitored and promoted. We decided to evaluate compliance to antimicrobial drugs in this study. Methods: In a cross-sectional study, 100 patients referring to 4 different specialists' offices were enrolled. The rate and type of non prescribed antibiotic administration were evaluated using predesigned questionnaires. The data were analyzed by SPSS 17.0 software using descriptive statistics and chi-square test for categorical data. Results: Our results showed that 62.4% of the study population had poor compliance and 37.6 % had good compliance with their prescribed regimen. "Feeling better "and "getting worse" on prescribed regimen were major reasons for drug discontinuation. About 70% of our study population get non prescribed antibiotic from pharmacies at least once a year. Most of the requested antibiotics were not first line options. Level of education was the only factor significantly related to the rate of patient compliance. Conclusion: This study shows the high rate of non prescribed antibiotic administration and low rate of compliance among the study population that emerge the need for particular patient education and putting restrictive rules to bound  non-prescribed and unsupervised  antibiotic marketing.